POTRET GERAKAN LITERASI SEKOLAH MENENGAH ATAS PADA MASA PANDEMI COVID 19 - Maria Rosalinda Talan; Metropoly Merlin J. Liuban; Joni Soleman Nalenan (Institut Pendidikan Tapanuli Selatan, 2022)
The COVID-19 pandemic also provides challenges in the world of education. Since the School Literacy Movement (GLS) has been integrated into the curriculum, it is deemed necessary to continue to run during the pandemic. This study aimed at describing the implementation of the GLS at SMA Negeri 1 Kefamenanu during the pandemic. The techniques used in colleting the data were questionnaires and observation. The data analysis technique used a flow model. The results showed that the implementation of the GLS at SMA Negeri 1 Kefamenanu during the pandemic was still running at the habituation stage through a face-to-face and Learning from Home (BdR) system. However, teachers and students admitted that that the BdR system was not optimal due to the limited range of supervision from the teachers. In general, the implementation of the GLS during the pandemic at SMA Negeri 1 Kefamenanu included three activities, namely 1) creating a literacy-friendly physical environment; 2) creating a social and affective environment as a model of communication and a literate interaction; and 3) creating school as a literate academic environment.